Betulinic acid increases lifespan and stress resistance via insulin/IGF-1 signaling pathway in Caenorhabditis elegans - Chen, Haiyan; Li, Rongji; Zhao, Feng; Luan, Li; Han, Tiantian; Li, Zhong (Frontiers in Nutrition, 2022)
Numerous studies reported that betulinic acid (BA), a natural product extracted from birch bark, exhibited various beneficial effects in vitro. However, its pharmacological activities in aging are rarely understood. In this study, C. elegans was deployed as a whole animal model to investigate the impacts of BA on lifespan and stress resistance. Wild-type C. elegans were fed in the presence or absence of BA and tested for a series of phenotypes, including longevity, mobility, reproductive capacity, pharyngeal pumping, heat stress, and oxidative stress. BA at the optimal dose (50 μg/mL) extended the lifespan, improved the healthspan, and significantly evoked the increased oxidative stress resistance in C. elegans. Incorporating the genetic analysis with different types of longevity mutants, DAF-16, the downstream effector of the Insulin/IGF-1 receptor signaling, was revealed to mediate the protective effects of BA on lifespan and antioxidant activity. Together, these data showcased the potential of BA in promoting healthy aging, which shall facilitate its further development in the food and pharmaceutical industries.